In-situ observation of cooperative grain boundary sliding and migration in the nano-twinned nanocrystalline-Au thin-films. (15th April 2020) - Li, Qizhen; Wang, Lihua; Teng, Jiao; Pang, Xiaolu; Han, Xiaodong; Zou, Jin
Abstract: Using our homemade tensile device inside a transmission electron microscope, we in-situ investigated the deformation behaviours of the nano-twinned nanocrystalline Au thin-films with thickness of 15 nm and average grain size of 16 nm. Our extensive in-situ observation studies reveal that the deformation of the nano-twinned nanocrystalline Au thin-film was dominated by the cooperative grain boundary sliding and migration, which were rarely observed in the previous reports. Meanwhile, our statistic shows that the nano-twins tended to promote further stress-driven grain growth, and the promotion became more remarkable for the nano-twinned grains that were located at the crack tips. Graphical abstract: Image, graphical abstract